2016
DOI: 10.1007/s10517-016-3525-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Reaction to Low-Intensity Laser Exposure by Its Solid Phase Structure

Abstract: The effects of various modes of low-intensity laser exposure on the sera of healthy subjects and patients are studied. It is shown by the cuneiform dehydration method that the serum structure is liable to change in response to certain modes of low-intensity laser exposure. The structure of patients' sera is more sensitive to low-intensity laser exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Martusevich et al agreed with this concept, suggesting that the pattern left behind from a blood drop is dependent on a person's health. They noted that characteristics of the blood patterns from a healthy person differed from those with a blood disease, for example, both hepatitis B and C. Differences between the blood serum patterns of healthy individuals, and those of patients with gastrointestinal and cardiovascular diseases have been observed in other studies . Brutin et al showed that samples from various patients – healthy, anaemic and hyperlipidemic—resulted in distinguishable patterns.…”
Section: Biofluid Pattern Analysis For Disease Diagnosismentioning
confidence: 94%
“…Martusevich et al agreed with this concept, suggesting that the pattern left behind from a blood drop is dependent on a person's health. They noted that characteristics of the blood patterns from a healthy person differed from those with a blood disease, for example, both hepatitis B and C. Differences between the blood serum patterns of healthy individuals, and those of patients with gastrointestinal and cardiovascular diseases have been observed in other studies . Brutin et al showed that samples from various patients – healthy, anaemic and hyperlipidemic—resulted in distinguishable patterns.…”
Section: Biofluid Pattern Analysis For Disease Diagnosismentioning
confidence: 94%
“…Analysis of the drying of biological fluids has shown that variations in solute type, and concentration, can create distinct deposition patterns with promising implications for rapid disease screening and diagnostics . Positive responses to treatments were also identifiable in the patterns formed from dried blood serum of patients with gastrointestinal disease . Functionalized gold nanoparticles have been shown to produce self-assembled crystalline lattice structures with enhanced light absorption in thin layers suitable for high-efficiency solar cells and other such structures with potential useful applications.…”
Section: Introductionmentioning
confidence: 99%
“… 35 Positive responses to treatments were also identifiable in the patterns formed from dried blood serum of patients with gastrointestinal disease. 36 Functionalized gold nanoparticles have been shown to produce self-assembled crystalline lattice structures with enhanced light absorption in thin layers suitable for high-efficiency solar cells 37 and other such structures with potential useful applications. The engineering of surfaces with antiviral properties 38 and allergen detection in foods 39 are additional examples of the many applications that stem from the self-assembly of nanoparticles within droplets.…”
Section: Introductionmentioning
confidence: 99%